Freiarbeit im DaF-Unterricht in der Grundschule - Möglichkeiten und Grenzen - Ržišnik Martinec, Anja (Vestnik za tuje jezike, 2019)
German as a foreign language class is an optional subject at elementary schools in Slovenia, one that is often attended by students of mixed ages and with varying knowledge of the language, and this is challenging for both teachers and students. The national curriculum for this subject often refers to this issue as well. For this reason the authors of the curriculum suggest a holistic approach to teaching and learning, one that involves the students in the learning process, from planning to evaluation. Free work is a didactic approach which makes the teaching and learning process easier due to its principles of free choice, self-correction, movement in learning and language materials, which together enable high levels of inner differentiation. It is a form of Open Learning (Ger. Off-ener Unterricht) that follows the line of New Education which puts in focus self-regulated, mainly individual learning in a prepared environment. The aim of this article is to present free work in German language classes from a theoretical and practical point of view, considering the limitations and possibilities of this approach when applied in public schools. Furthermore, the article presents proven free work materials for young foreign language learners that can be produced and used by foreign language teachers.
Keywords: didaktika jezika; Freinet, Georges; Montessori, Maria; nemščina; odprti pouk; osnovna šola; prosto delo; tuji jeziki